Clinical predictors of hypoxemia in pneumonia - Eka Gunawijaya; I M Widia (Indonesian Pediatric Society Publishing House, 2016)
Background Pneumonia is one of the main causes of death in infants in developing countries. The device of oxygen saturation measurement for detecting hypoxemia is limited in district hospi- tals. Objective The aim of our study was to find the best clinical pre- dictor for hypoxemia that could be used in Indonesia. Methods Between June 2001 until May 2002, the diagnostic test was performed in 125 infants aged 2-12 month-old who suffered from pneumonia. The oxygen saturation measured by pulse oxim- etry was used as the gold standard. Results The samples were divided into two groups, 52 infants with hypoxemia and 73 normal. The base characteristics of both groups were not statistically different. The prevalence of hypoxemia was 41.6%. The best single clinical predictor of hypoxemia was cyano- sis (the sensitivity 92%, specificity 86%, likelihood ratio 6.74, post- test probability 83%), as well as the combination of two clinical predictors i.e., cyanosis and nasal flaring. The best combination of three clinical predictors was cyanosis, nasal flaring, and refusal to drink (the sensitivity 92%, specificity 86%, likelihood ratio 6.74, post-test probability 81%). Conclusion The combination of cyanosis and nasal flaring is good enough as a predictor to detect hypoxemia in area with no facility of oxygen saturation measurement